Topical vs. Intralesional Drug Delivery Systems in Hypertrophic Scar Management: A Comparative Study Using Nanocarrier-Based Formulations - Shree, Anu; Sinha, Dr. Keshav Kumar (Student’s Journal of Health Research Africa, 2024)
Background Hypertrophic scars pose considerable aesthetic and functional difficulties, frequently arising from trauma, burns, or surgical procedures. Current treatment modalities encompass both topical and intralesional therapies; however, emerging drug delivery platforms, such as nanocarrier-based systems, present innovative strategies to improve therapeutic efficacy. This study evaluates the efficacy and safety of topical versus intralesional administration of nanocarrier-based corticosteroid formulations, concentrating on treatment response, scar regression, and patient adherence. Objective: To assess and contrast the therapeutic efficacy of topical versus intralesional nanocarrier-mediated corticosteroid therapies in individuals with hypertrophic scars. Methods This prospective, comparative interventional study was performed at Patna Medical College and Hospital, involving 60 patients diagnosed with hypertrophic scars. Participants were randomly assigned to two groups: Group A received a topical liposomal corticosteroid gel, while Group B received an intralesional corticosteroid suspension encapsulated in ethosomal nanocarriers. The treatment response was evaluated using the Vancouver Scar Scale (VSS) at baseline and during periodic follow-ups over a one-year period. Adverse events, patient-reported outcomes, and satisfaction were documented as well. Results Both groups exhibited a statistically significant decrease in VSS scores following treatment (p < 0.05). Nevertheless, the intralesional group exhibited a more rapid onset of improvement, especially regarding scar height and vascularity. The topical nanocarrier group was preferred due to its pain tolerance, compliance, and lack of injection-related complications. No systemic adverse effects were noted in either cohort. Conclusion Both topical and intralesional nanocarrier-based drug delivery systems are efficacious in the management of hypertrophic scars. Intralesional therapy facilitates rapid and significant scar regression, whereas topical nanocarrier systems present a non-invasive, patient-friendly option with satisfactory therapeutic effectiveness. Customizing therapy according to scar attributes and patient preferences may improve clinical results.